2023
DOI: 10.3390/economies11010024
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity Creation and Economic Growth: Are They Monotonically Related? Evidence from MENA Countries

Abstract: Over the period 2000–2019, we reexamine the connection between finance, as measured by one of the primary banking sector functions—liquidity creation (LC)—and economic growth (EG) in 10 MENA countries panel. In a scenario seen as a dynamic heterogeneous panel, pooled mean group estimates demonstrate that LC and EG may have a favourable long-run connection while also having no influence in the short-run. In addition, results reveal an inverted U-shaped link between LC and EG over the short-term and long-term. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
0
0
0
Order By: Relevance
“…This study examines the impact of TLCPC of FIBs, HCBs and PCBs on real economic output in a sample of 12 Muslim-majority countries (4 with dual banking system and 8 with tri-banking system) using the FGLS framework over the period of 10 years from 2013 to 2022. Our study extends the limited literature on the impact of the banking system liquidity creation on economic activity (Almeshari et al , 2023; Beck et al , 2023; Berger and Sedunov, 2017; Fidrmuc et al , 2015; Umar et al , 2021) by providing new evidence from Muslim-majority countries with dual banking system and tri-banking system. Our findings show that liquidity created by HCBs to have greater impact on real economic output compared to that created by FIBs and PCBs.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…This study examines the impact of TLCPC of FIBs, HCBs and PCBs on real economic output in a sample of 12 Muslim-majority countries (4 with dual banking system and 8 with tri-banking system) using the FGLS framework over the period of 10 years from 2013 to 2022. Our study extends the limited literature on the impact of the banking system liquidity creation on economic activity (Almeshari et al , 2023; Beck et al , 2023; Berger and Sedunov, 2017; Fidrmuc et al , 2015; Umar et al , 2021) by providing new evidence from Muslim-majority countries with dual banking system and tri-banking system. Our findings show that liquidity created by HCBs to have greater impact on real economic output compared to that created by FIBs and PCBs.…”
Section: Discussionsupporting
confidence: 56%
“…This positive relationship between liquidity creation and economic growth has recently been affirmed using a global data set at both country and industry levels by Beck et al (2023). However, Almeshari et al (2023) have reported a nonlinear relationship between liquidity creation and economic growth in a sample of 10 MENA countries. Finally, Umar et al (2021) found a negative relationship between liquidity creation and economic output in the case of China.…”
Section: Literature Reviewmentioning
confidence: 79%
See 1 more Smart Citation
“…Ali and Mughal et al (2023) inspected the effect of monetary policy on the bank's liquidity creation. Studies specific to the MENA region have demonstrated a positive influence of finance on economic growth (Almeshari et al, 2023;Boukhatem & Ben, 2018). However, earlier studies, such as those conducted by Beck et al (2023) and Gazdar and Cherif (2015) and, have indicated either an adverse effect or an inconsequential affiliation between finance and GDP.…”
Section: Literature Reviewmentioning
confidence: 99%